PREPARATION AND CHARACTERIZATION OF MICROCRYSTALLINE CELLULOSE FROM OIL PALM FROND BY CHEMICAL AND MECHANICAL TREATMENT - Randis, Randis; Darmadi , Djarot B.; Gapsari , Femiana; Sonief , Achmad As’Ad; Rus , Tatag Yufitra (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Oil palm fronds are currently an underutilised by product of plantations. The micro and nano cellulose can be utilised to create new goods, such as being used as a filler in environmentally friendly degradable composites. This study examined the process of extracting oil palm frond fiber (OPFF) by using a series of chemical and mechanical treatments to get pure microcrystalline cellulose (MCC). The MCC obtained by OPFF was subsequently analysed in further detail. The identification of morphological analysis, presence of functional groups, and crystallinity index were conducted using Scanning Electron Microscopy (SEM), Fourier Transform InfraRed (FTIR) and X-Ray Difraction (XRD) techniques. The findings revealed the presence of microcrystalline structures in OPF fibers, having a mean measurement of width 3.2 ± 0.42 ?m. The application of FTIR verified that the elimination of noncellulosic constituents from the treated OPF fibers had achieved its utmost level. Simultaneously, X-ray diffraction research revealed that the utilization of chemical procedures resulted the formation of a characteristic cellulose crystal structure and an augmentation in the crystallinity index. However, the mechanical treatment resulted in a minor drop in the crystalline index. This can be ascribed to the disturbance of cellulose chains and the crystal structure within the cellulose fibers. The cellulose obtained from raw fibers and subsequent processing exists in a very pure form, specifically in the cellulose I? structure. This enables its utilization as reinforcement in eco-friendly MCC-based green composites, offering numerous benefits.